A simple electroanalytical method for the analysis of the dye solvent orange 7 in fuel ethanol - Romanini, Daiane Cristina [UNESP]; Goncalves Trindade, Magno Aparecido [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2009)
The purpose of this paper is to develop a simple, rapid and accurate electroanalytical method for the determination of solvent orange 7 (SO-7), commercially used as a dye marker in fuel ethanol samples. SO-7 is oxidized in a mixture of Britton-Robinson buffer with N,N-dimethylformamide (1: 1, v/v) at a glassy carbon electrode and presents a well-defined peak around +0.70 V vs. Ag/AgCl, which can be monitored by linear-scan voltammetry (LSV) and square-wave voltammetry (SWV). Using optimized parameters based on the SWV technique, it is possible to get a linear relationship between the peak current and the SO-7 dye concentration from 4.0 x 10(-6) to 18.0 x 10(-6) mol L(-1) (r = 0.995). The proposed method was successfully applied to the direct quantification of the SO-7 dye in fuel ethanol samples, which gave good average recovery for commercial samples containing 5.0 mg L(-1) and 10.0 mg L(-1) of SO-7 dye, respectively. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Solvent orange 7; Fuel ethanol; Electroanalytical method; Dye marker; Analysis of dye